The analysis of characteristics of anti-SARS-CoV-2 antibodies in clinically COVID-19 patients - Wenzheng Guo; Siyuan Yu; Guangbo Li; Qiankun Xuan; Simin Yang; Donghua Wen; Wenjuan Wu (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Background: The novel coronavirus disease (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), had spread all of China and many other countries. The COVID-19 patients exhibit typical clinical symptoms, and most cases could be diagnosed by nucleic acid testing and imaging. Recent studies have reported that serum antibody testing can be used for diagnostic screening of SARS-CoV-2 infection. However, the rules and standards of antibody production in serum of discharged COVID-19 patients remain ambiguous.  Methods: We examined both nucleic acid and antibody detection of 139 non-severe (mild and common) patients who were diagnosed with COVID-19. Results: Although the nucleic acid of the discharged patient has turned to negative, some patients have not detected antibodies, including IgG (n=11) and IgM (n=27) .19.4% (27/139) discharged patients' IgM detection was negative. In the IgM positive discharged patients, 72.8% (83/114) have an onset time over 30 days. And, there was no statistically significant difference in IgM concentration of discharged patients from 4 to 9 weeks after the onset of disease. In addition, we also detected IgM and IgG in nucleic acid test positive patients (n=12) within two weeks after the onset of disease. The concentration of IgM was peaked about on the sixth day and then decreased, while the IgG concentration was continuously increasing.  Conclusions: Our study demonstrated the rules and standards of antibody production in serum of discharged COVID-19 patients which will provide more ideas for COVID-19 research.